Oxygen transport kinetics underpin rapid and robust diaphragm recovery following chronic spinal cord injury - Warren, Philippa M; Kissane, Roger W P; Egginton, Stuart; Kwok, Jessica C F; Askew, Graham N (The Journal of physiology, 2021)
KEY POINTS: Spinal treatment can restore diaphragm function in all animals 1 month following C2 hemisection induced paralysis. Greater recovery occurs the longer after injury the treatment is applied. Through advanced assessment of muscle mechanics, innovative histology and oxygen tension modelling, we have comprehensively characterized in vivo diaphragm function and phenotype. Muscle work loops reveal a significant deficit in diaphragm functional properties following chronic injury and paralysis, which are normalized following restored muscle activity caused by plasticity-induced spinal reconnection. Injury causes global and local alterations in diaphragm muscle vascular supply, limiting oxygen diffusion and disturbing function. Restoration of muscle activity reverses these alterations, restoring oxygen supply to the tissue and enabling recovery of muscle functional properties. There remain metabolic deficits following restoration of diaphragm activity, probably explaining only partial functional recovery. We hypothesize that these deficits need to be resolved to restore complete respiratory motor function. ABSTRACT: Months after spinal cord injury (SCI), respiratory deficits remain the primary cause of morbidity and mortality for patients. It is possible to induce partial respiratory motor functional recovery in chronic SCI following 2 weeks of spinal neuroplasticity. However, the peripheral mechanisms underpinning this recovery are largely unknown, limiting development of new clinical treatments with potential for complete functional restoration. Utilizing a rat hemisection model, diaphragm function and paralysis was assessed and recovered at chronic time points following trauma through chondroitinase ABC induced neuroplasticity. We simulated the diaphragm's in vivo cyclical length change and activity patterns using the work loop technique at the same time as assessing global and local measures of the muscles histology to quantify changes in muscle phenotype, microvascular composition, and oxidative capacity following injury and recovery. These data were fed into a physiologically informed model of tissue oxygen transport. We demonstrate that hemidiaphragm paralysis causes muscle fibre hypertrophy, maintaining global oxygen supply, although it alters isolated muscle kinetics, limiting respiratory function. Treatment induced recovery of respiratory activity normalized these effects, increasing oxygen supply, restoring optimal diaphragm functional properties. However, metabolic demands of the diaphragm were significantly reduced following both injury and recovery, potentially limiting restoration of normal muscle performance. The mechanism of rapid respiratory muscle recovery following spinal trauma occurs through oxygen transport, metabolic demand and functional dynamics of striated muscle. Overall, these data support a systems-wide approach to the treatment of SCI, and identify new targets to mediate complete respiratory recovery.
Keywords: kinetika; Rats; poranění míchy; bránice; potkani Sprague-Dawley; obnova funkce; nervus phrenicus; spinal cord injury; krysa rodu Rattus; mechanical properties; angiogenesis; kyslík; zvířata; Humans; Recovery of Function; diaphragm; Phrenic Nerve; Kinetics; Spinal Cord; Diaphragm; Rats, Sprague-Dawley; Oxygen; capillary domain area; Spinal Cord Injuries; mícha; lidé; Animals